The expression of the person’s criminal behaviour in Ukrainian general language phraseology (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
In the article the ideographical analysis of thematic group of phraseology units is carried out on denotation of person’s criminal behavior: basic variant and synonymous groups are determined, the motivational base of such expressions is found out.
Keywords: anthropocentrism; pejorativity; ideographic description; variant-synonimic group